2016
DOI: 10.1177/1073191116648209
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Nomothetic and Idiographic Approaches to the Analysis of Clinical Data

Abstract: The nomothetic approach (i.e., the study of interindividual variation) dominates analyses of clinical data, even though its assumption of homogeneity across people and time is often violated. The idiographic approach (i.e., the study of intraindividual variation) is best suited for analyses of heterogeneous clinical data, but its person-specific methods and results have been criticized as unwieldy. Group iterative multiple model estimation (GIMME) combines the assets of the nomothetic and idiographic approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
198
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(216 citation statements)
references
References 49 publications
(89 reference statements)
3
198
0
6
Order By: Relevance
“…Although the current sample was highly heterogeneous by design, we anticipate based on past experience using GIMME in several data sets of different sorts (Beltz et al, 2016;Price et al, 2017) that massive heterogeneity is likely to be the rule rather than the exception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the current sample was highly heterogeneous by design, we anticipate based on past experience using GIMME in several data sets of different sorts (Beltz et al, 2016;Price et al, 2017) that massive heterogeneity is likely to be the rule rather than the exception.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly the case in clinical settings (i.e., mental health), although this could be extended to occupational or other healthcare settings. The main engine of the GIMME approach, uSEM, can be estimated for an individual (For exemplars see Beltz et al, 2016;Fisher et al, in press;or Foster & Beltz, in press), and the GIMME software package includes this capability. This makes it feasible to apply this model using the same tools in practical settings using easy to use and freely available software.…”
Section: Implications For Applied Assessmentmentioning
confidence: 99%
“…These co-influential interactions produce differential effects that can be studied and understood at both an individual and subgroup level over time (e.g., Beltz, Wright, Sprague, & Molenaar, 2016;Kremer, Flower, Huang, & Vaughn, 2016).…”
Section: Schoolsmentioning
confidence: 99%
“…Consistent with these expectations, time series network analyses of depression symptoms differ from cross-sectional analyses (Bringmann, Lemmens, Huibers, Borsboom & Tuerlinckx, 2015;Fried et al, 2016), and individuals have been found to have highly distinct networks of associations among domains of psychopathology (Beltz, Wright, Sprague, & Molenaar, 2016;Wright, Beltz, Gates, Molenaar & Simms, 2015). These assumptions evidently require further investigation.…”
Section: Violated Theoretical Assumptionsmentioning
confidence: 88%